ANALYSIS OF BRAND IMAGE, PRICE, QUALITY, PROMOTION, AND CONSUMER ATTITUDE ON REPURCHASE INTENTION THROUGH PURCHASE DECISION IN TOKOPEDIA - Alhadi Pratama; Rosdiana Sijabat (Journal of Global Business and Management Review, 2026)
The e-commerce business in Indonesia is very competitive, with market share positions frequently changing. In a competitive market, market leaders' positions fluctuate quickly, as Tokopedia discovered. This study aimed to determine whether brand image, product quality, consumer attitudes, and promotions influence purchase decisions as mediating variables on repurchase intention on the Tokopedia marketplace. The present study is a quantitative study that used a causal study approach with Tokopedia e-commerce users. The findings of this study show that all hypotheses are accepted, implying that brand image, product quality, consumer attitudes, and promotions influence purchase decisions and consumer repurchase intentions.